Development of Local Foodstuff-Based Complementary Food Porridge MP-ASI "SITOLE" Products as an Effort to Manage Stunting - Waryana, Waryana; Wijanarka, Agus; Fadhilah, Dina (JURNAL INFO KESEHATAN, 2023)
One of the causes of stunting is poor nutritional intake in infancy and recurrent illnesses due to an unhealthy environment. Mothers of under-five children are the potential strategic target to be empowered to manage stunting. They have to be empowered to meet nutritional needs during infancy. Complementary breast milk food containing calcium, zinc, selenium, iodine, Fe, protein, and phosphorus can be developed using local foodstuffs. This study aimed to investigate the impact of community empowerment training on the knowledge improvement of mothers regarding the development of locally sourced complementary feeding products (MP-ASI) as an intervention to address stunting issues and to formulate a nutrient-rich complementary food product for infants aged 6-12 months. The research design employed was a quasi-experimental study with a pre-and post-test with a control group design. The study subjects were mothers with infants aged 6-12 months residing in Triharjo Village, Kapanewon Pandak, who met the inclusion criteria and were willing to participate. Mothers who were unable to read and write were excluded from the study. The study was conducted in Triharjo Village, Kapanewon Pandak, Bantul, from April to July 2022. A total of 54 respondents, selected through simple random sampling, were included as the study sample out of 100 families population. Knowledge data were collected using a questionnaire as the data collection instrument and analyzed using the Dependent T-Test and Independent T-Test at a 95% confidence level. The results indicated a significant difference in knowledge improvement (delta) between the treatment and control groups. A locally sourced complementary food product for infants aged 6-12 months, named "SITOLE" porridge, was developed as an outcome. The development data of the MP-ASI product (Sitole porridge) were compiled using a group discussion method.